Association between Allelic Variations of -174G/C Polymorphism of Interleukin-6 Gene and Chronic Kidney Disease-Mineral and Bone Disorder in Iraqi Patients (Baghdad Science Journal, 2020)
This study designed to examine association between-174G/C polymorphism of interleukin-6 gene and phosphate, calcium, vitamin D3, and parathyroid hormone levels in Iraqi patient with chronic kidney disease on maintenance hemodialysis. Seventy chronic renal failure patients (patients group) and 20 healthy subjects (control group) were genotyped for interleukin-6 polymorphism and genotyping was performed by conventional polymerase chain reaction-restriction fragment length polymorphism. No significant differences in phosphate levels were observed in patients and control with different interleukin-6 genotypes. Control had non-significant differences in calcium levels, while patients with GG and CG genotypes displayed significant elevation with time. Conversely, control and patients with GG and CC genotypes had significant elevation in vitamin D3 levels with time. Regarding parathyroid hormone, control had non-significant differences, while patients with GG and CC genotypes displayed significant elevation with time.Patients with GG genotype displayed significant changes in calcium, vitamin D3 and parathyroid hormone levels with time.